Correlation of HER2 with Stages of Carcinoma Stomach - Tani, Sadia Afrin; Hossain, ABM Bayezid; Jahan, Ishrat; Faruk, Imtiaz; Farhad Ul Hasan, ASM; Sultana, Salma; Kumar Das, Tapas; Azad, Md Abul Kalam (Journal of Surgical Sciences, 2025)
Background: The variability of prognosis within a clinical & pathological stage of gastric cancer, underscores the need for specific biological markers to identify subgroups of patients for intensive treatment. The purpose of this study was to evaluate the correlation between HER2overexpression with different stages of carcinoma stomach. To our knowledge, this is the first study from Bangladeshi population reporting on the relationship of HER-2 expression with different stages of carcinoma stomach. Methods: This cross-sectional study included 53 patients with gastric cancer who underwent surgery at different Hospital in Dhaka city between November 2016 and October 2017. All the patients were clinically staged before surgery & tumor samples were examined for HER2 expression by immunohistochemistry (IHC). The results correlated with clinicopathological features & stages of carcinoma stomach. Percentage expression for positivity of HER2 was estimated along with 95% confidence interval. The differences in the positivity rate between different sex, stages and grades were tested through ‘Chi’ square test of significance and a value of p <0.05 was consider to be statistically significant. Results: The mean age was 51.74±12.02 years, more than half (52.8%) patients were male. Almost two third (66.0%) patients had tumor location in antrum and more than three fourth (79.2%) patients had intestinal type carcinoma. Regarding the Staging it was observed that 21(39.6%) patients had T =staging 4b, 33(62.3%) N=staging 1 and 16(30.2%) M=staging 1. Nearly two third (66.0%) patients had grading 2. More than three fourth (75.5%) patients had HER2 scoring 0/1+ Negative, followed by 10(18.8%) had 3+ positive and 3(5.7%) had 2+ equivocal. Statistically no significant association (p>0.05) were found betweenHER-2 positive group with age, gender and tumor location. More than three fourth (80.0%) patients had intestinal type and 2(20.0%)had diffuse type histological pattern in HER2 positive group, which was statistically significant (p<0.05). More than three fourth (80.0%) patients had T =staging 4b in positive group and 13(30.2%) in negative group. More than two third (70.0%) had N=staging 1 in positive group and 26(60.4%) in negative group. More than three fourth (80.0%) M=staging 1 in positive group and 8(18.6%) in negative group. The difference of T =staging and M=staging was statistically significant (p<0.05) between two groups. Though there was no significant association with tumor grading. Conclusion: The patients of gastric cancer with HER2 overexpression constitute a distinct subgroup. In this study HER2 overexpression was significantly associated with Intestinal type, T & M staging but not with N staging. Thus it evident that HER2 status is associated with advanced stages of gastric carcinoma. Journal of Surgical Sciences (2021) Vol. 25 (1) : 42-46